Utility of balloon aortic valvuloplasty in the transcatheter aortic valve implantation era - Dawson, Luke (Open Heart, 2020)
BACKGROUND: Balloon aortic valvuloplasty (BAV) has seen renewed interest since the advent of transcatheter aortic valve implantation (TAVI). The study aimed to characterise a contemporary BAV cohort and determinants of clinical outcomes. METHODS: Patients undergoing BAV at a single tertiary centre were retrospectively reviewed over a 10-year period, and functional and mortality outcomes were reported with up to a 2-year follow-up. RESULTS: 224 patients (aged 82.5±8.3 years; 48% female) underwent BAV over the study period. Indications were either destination treatment (39%) or bridge-to-valve replacement (61%)—including bridge-to-decision (29%), symptom relief while on the waitlist (27%), and temporary contraindications to TAVI/aortic valve replacement (AVR) (5%). The mean reduction of aortic mean pressure gradient was 38%. Procedural mortality occurred in 0.5%, stroke in 1.3%, and major bleeding in 0.9%. Twelve-month mortality was 36% overall, and 26% and 50% in the bridging and destination groups, respectively. New York HeartAssociation (NYHA) class improved by ≥1 at 30 days in 50%. Among the bridge-to-TAVI/AVR group, 40% proceeded to TAVI/AVR within 12 months following BAV. In multivariate analysis, active malignancy at baseline (OR: 4.4, 95% CI: 1.3 to 15.1, p=0.02), smoking history (OR: 3.3, 95% CI: 1.3 to 7.9, p<0.01), LVEF ≤30% at baseline (OR: 3.2, 95% CI: 1.3 to 7.6, p<0.01), destination treatment (OR: 2.2, 95% CI: 1.0 to 4.9, p=0.04) were all associated with 12-month mortality. CONCLUSIONS: BAV remains a useful procedure with relatively low rates of complications, however, 1-year mortality rates are high. Contemporary indications for BAV include a bridge to definitive valve replacement or destination treatment.